COVID-19 and hyperglycemia/diabetes - Michalakis, Konstantinos (World J Diabetes, 2021)
In early studies regarding coronavirus disease 2019 (COVID-19), type 2 diabetes mellitus was considered to contribute substantially to the disease’s inflammatory response. Subsequently, even hyperglycemia, regardless of insulin resistance or diabetes mellitus, was found to be additionally harmful. Recent studies have shown inflammation of the pancreatic β cells in COVID-19, even leading to new onset diabetes mellitus. We hereby summarize core literature on glycemia and COVID-19, and present implicated pathways and mechanisms.